CRM197-conjugated peptides vaccine of HCMV pp65 and gH induce maturation of DC and effective viral-specific T cell responses. Issue 1 (31st December 2023) - Zhang, Shuyun; Nan, Fulong; Jiang, Shasha; Zhou, Xiaoqiong; Niu, Delei; Li, Jun; Wang, Hui; Zhang, Xueming; Zhang, Xianjuan; Wang, Bin
ABSTRACT: Human cytomegalovirus (HCMV) infection is prevalent worldwide, and there is currently no licenced HCMV vaccine to control it. Therefore, developing an effective HCMV vaccine is a significant priority. Because of their excellent immunogenicity, the crucial components of HCMV, phosphoprotein 65 (pp65) and glycoproteins H (gH) are potential target proteins for HCMV vaccine design. In this study, we predicted and screened the dominant antigenic epitopes of B and T cells from pp65 and gH conjugated with the carrier protein cross-reacting material 197 (CRM197) to form three peptide-CRM197 vaccines (pp65-CRM197, gH-CRM197, and pp65-CRM197+gH-CRM197). Furthermore, the immunogenicity of the peptide-CRM197 vaccines and their effects on dendritic cells (DCs) were explored. The results showed that three peptide-CRM197 vaccines could induce maturation of DCs through the p38 MAPK signalling pathway and promote the release of proinflammatory factors, such as TNF-α and interleukin (IL) −6. Meanwhile, the peptide-CRM197 vaccines could effectively activate T cell and humoral immunity, which were far better than the inactivated HCMV vaccine. In conclusion, we constructed three peptide-CRM197 vaccines, which could induce multiple immune effects, providing a novel approach for HCMV vaccine design.